Distorsi Kewarasan dan Analisis Perkembangan Tokoh Utama dalam Novel Assavella dan Ballerina (Assavella 2): Perspektif Psikologi - Salma, Mardiatu; Alsunah, Aditya Ansor; Nurwahidah, Lina Siti; Julianto, Cecep Dudung (eScience Humanity Journal, 2025)
The research entitled Sanity Distortion and Analysis of Main Character Development in the Novels Assavella and Ballerina (Assavella 2): A Literary Psychology Perspective aims to reveal the form of sanity distortion and the psychological development of the main characters through a literary psychology approach. These two Wattpad novels depict trauma, inner conflict, and social pressure that affect the mental condition of the characters. This research is a literature study with a qualitative descriptive method. Data in the form of narrative texts, dialogues, and monologues were collected through reading and note-taking methods. The results of the study show that the main character experiences sanity distortion due to past trauma and social pressure in Assavella, then shows the process of recovery and self-acceptance in Ballerina (Assavella 2). Thus, both novels represent a psychological journey from destruction to awareness and self-healing.